Multi-session tDCS over the posterior parietal cortex and associative memory - Luka Juras; Marina Martinčević; Uroš Konstantinović; Saša R. Filipović; Andrea Vranić; Jovana Bjekić (PLoS ONE, 2025)
Associative memory (AM) plays a crucial role in our ability to link disparate elements of our experiences, yet it is especially vulnerable to age-related decline and pathological conditions. Non-invasive brain stimulation (NIBS), particularly transcranial direct current stimulation (tDCS), has been investigated as a potential intervention to enhance cognitive functions, including AM. Previous tDCS studies yielded inconsistent results, often due to variations in stimulation sites and protocols. Nonetheless, enough evidence suggests that tDCS over the posterior parietal cortex (PPC) can improve AM performance. This study aimed to investigate the cumulative effects of multiple anodal tDCS over the PPC on AM performance alongside item memory and verbal fluency. In a randomized sham-controlled trial, 59 healthy young adults were assigned to either anodal or sham stimulation group, receiving tDCS (1.5 mA, for 20 minutes, at P3) over three consecutive days. Memory performance was assessed at four timepoints: pretest, immediately after the first session, posttest (Day 5), and follow-up (Day 9). Although tDCS was well tolerated, the anticipated enhancement of memory performance was not observed. We interpret these findings in the light of methodological considerations and propose potential explanations for the observed results emphasizing the large between-participants variability in memory performance as a significant factor that may have hindered the detection of tDCS effects.